Proceedings of the 2025 4th International Conference on Educational Innovation and Multimedia Technology (EIMT 2025) - Heyong Wang; Yinyin Xiao; Mustafa Misir; Dayana Farzeeha Ali (Atlantis Press International BV, 2025)
This is an open access book. As a leading role in the global megatrend of scientific innovation, China has been creating a more and more open environment for scientific innovation, increasing the depth and breadth of academic cooperation, and building a community of innovation that benefits all. Such endeavors are making new contributions to the globalization and creating a community of shared future. To adapt to this changing world and China's fast development in the new era, 2025 4th International Conference on Educational Innovation and Multimedia Technology (EIMT 2025) to be held in March 14–16, 2025. This conference takes'bringing together global wisdom in scientific innovation to promote high-quality development'as the theme and focuses on cutting-edge research fields including Educational Innovation and Multimedia Technology. EIMT 2024 encourages the exchange of information at the forefront of research in different fields, connects the most advanced academic resources in China and the world, transforms research results into industrial solutions, and brings together talent, technology and capital to drive development. The conference sincerely invites experts, scholars, business people and other relevant personnel from universities, scientific research institutions at home and abroad to attend and exchange!